AN AMBISPECTIVE STUDY ON ATAXIA PATIENTS ADMITTED IN NEUROLOGY DEPARTMENT OF A TERTIARY CARE HOSPITAL - Sk. Jaheda Begum; G. Bindu Narmada; G. Venkata Vagdevi; K. Pardha Saradhi; C. Pavan Sai; B. Pravallika (The Bioscan, 2025)
BACKGROUND: Ataxia refers to impaired motor control, often described as incoordination, which hampers the ability to perform smooth, controlled movements. This condition can impact various functions, including speech, swallowing, walking, balance, hand-eye coordination, and eye movements. The primary objective of this study is to assess the relationship between different types of ataxias and their underlying causes, risk factors, associated conditions, and distinguishing characteristics. METHODOLOGY: Over six months, an ambispective observational study conducted at a tertiary care hospital identified ataxia in 48 out of 850 patients. Data were collected from both inpatient and outpatient neurology departments. Statistical methods, including the chi-square test, were applied to analyze and tabulate the data, leading to the study’s findings. RESULTS: Our study revealed that ataxia was more prevalent among males, primarily in the age group of 31–45 years. The majority of subjects (91.6%) exhibited unsteady gait. Notably, a significant proportion (68.75%) were born to parents in consanguineous marriages, indicating a potential correlation. Additionally, clinical parameters such as alcohol consumption, tobacco smoking, hypertension, and a family history of ataxia demonstrated significant interdependence. CONCLUSION: The study identified middle-aged males as the most commonly affected group, presenting with symptoms such as unsteady gait, poor coordination, imbalance, and slurred speech. Many of these individuals had comorbidities, including hypertension (HTN) and cerebrovascular accidents (CVA). While some clinical parameters showed correlations with the observed symptoms, no significant association was established between age, gender, etiology, and comorbidities. The study concluded that certain key clinical parameters might have meaningful associations warranting further investigation.